AtCPL5, a novel Ser-2-specific RNA polymerase II C-terminal domain phosphatase, positively regulates ABA and drought responses in Arabidopsis - Jin, Yong-Mei (The New phytologist, 2011)
© 2011 The Authors. New Phytologist © 2011 New Phytologist Trust.